Seed degeneration in potato: the need for an integrated seed health strategy to mitigate the problem in developing countries - Thomas-Sharma, Sara; Abdurahman, A.; Ali S; Andrade-Piedra, J.L.; Bao, S.; Charkowski A; Crook D; Kadian, M.S.; Kromann, P.; Struik, Paul C.; Torquebiau, Emmanuel F.; Garrett, K.A.; et al. (Wiley, 2016)
Seed potato degeneration, the reduction in yield or quality caused by an accumulation of pathogens and pests in planting material due to successive cycles of vegetative propagation, has been a long-standing production challenge for potato growers around the world. In developed countries this problem has been overcome by general access to and frequent use of seed, produced by specialized growers, that has been certified to have pathogen and pest incidence below established thresholds, often referred to as certified seed. The success of certified seed in developed countries has concentrated the research and development agenda on the establishment of similar systems in developing countries. Despite these efforts, certified seed has had little penetration into the informal seed systems currently in place in most developing countries. Small-scale farmers in these countries continue to plant seed tubers acquired through the informal seed system, i.e. produced on-farm or acquired from neighbours or local markets. Informal seed tubers frequently have poor health status, leading to significant reductions in yield and/or market value. This review emphasizes the need to refocus management efforts in developing countries on improving the health status of seed tubers in the informal system by integrating disease resistance and on-farm management tools with strategic seed replacement. This ‘integrated seed health strategy’ can also prolong the good health status of plants derived from certified seed, which would otherwise be diminished due to potential rapid infection from neighbouring fields. Knowledge gaps, development challenges and impacts of this integrated seed health strategy are discussed.